Preliminary Study of Cinnamomum burmannii Extracts to Reduce Fasting Blood Glucose Level and Body Weight in Type-2-DM-Induced Rats - Claudia, Regita Almira; Sari, Shinta Dewi Permata; Safitri, Yolanda (Muhammadiyah Medical Journal, 2024)
Background: Diabetes mellitus prevalence in Indonesia tends to be elevated based on glucose measurement. Antidiabetic oral has some serious side effects for long-term use. Several studies explored various types of Cinnamomum extract's effects on antidiabetic activity and potentially became an alternative therapy in Diabetes mellitus patients. Purposes: This study aimed to determine Cinnamomum burmannii extract’s effect on body weight and fasting blood glucose level in rats induced Type-2 DM. Methods: This study was conducted at the Laboratory of the Faculty of Pharmacy and Science, University Muhammadiyah of Prof. DR. Hamka. This study design was a true experimental method by administering Cinnamon extract at 30mg/kg, 60mg/kg, 120mg/kg, and 200mg/kg to animal tests. The statistical analysis used a T-test to compare the different results in parameters before and after the administration of Cinnamon extract. Results: This study shows a difference in blood sugar level and body weight before and after the cinnamon extract group administration. The body weight results presented no significant differences between before and after administering Cinnamon extracts at doses of 30mg/kg, 60mg/kg, 120mg/kg, and 200mg/kg. In contrast, the blood sugar level showed significant differences between before and after administration of Cinnamon extract at group doses (p0.05). Metformin was still more influential in reducing fasting blood sugar than Cinnamomum burmannii extract at 30mg/kg. Conclusion: This study concluded that Cinnamomum burmannii extract with various doses could reduce fasting blood glucose levels and body weight. The highest dose showed a significant difference in fasting blood glucose levels before and after the administration of extracts.